Authentication of Study Material in E-Learning using Digital Signature Algorithms - Ghosh, A; Karforma, S (International Journal of Computer Sciences and Engineering, 2025)
Now-a-days ICT (Information and Communication Technology) is so much improved by using various network technologies so that any type of information can be send and received very easily. This information may be belongs to banking system, government oriented system or E-learning system. Security is highly needed to protect it from any unauthorized person. For security four things are required: confidentiality, integrity, authentication and non-repudiation. When a sender wants to send an electronic document to the receiver, an attacker can get it and modify it and send the altered document to that receiver. Digital Signature is applied to avoid such situations. Properly applied Digital Signature gives confident to the receiver that the document is reliable and was sent by the original sender. Thus Digital Signature provides not only the confidentiality and integrity of the document but also provides non-repudiation so that the signature can’t be denied by the signer. In this paper authors have discussed about the comparative study of different cryptographic Digital Signature algorithms such as RSA, DSA, ECDSA, GOST and ElGamal to achieve a better security for authenticity and integrity in E-Learning system during upload lecture notes between Teacher and Admin.